2016
DOI: 10.1016/j.crvi.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of efficient plant-growth-promoting bacteria isolated from Sulla coronaria resistant to cadmium and to other heavy metals

Abstract: The inoculation of plants with plant-growth-promoting rhizobacteria has become a priority in the phytoremediation of heavy-metal-contaminated soils. A total of 82 bacteria were isolated from Sulla coronaria root nodules cultivated on four soil samples differently contaminated by heavy metals. The phenotypic characterization of these isolates demonstrated an increased tolerance to cadmium reaching 4.1mM, and to other metals, including Zn, Cu and Ni. Polymerase Chain Reaction/Restriction Fragment Length Polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…(strain I10). Furthermore, intracellular Cd (II) bioaccumulation was found to be greater than that in the cell wall, demonstrating that Cd (II) bioaccumulation was related to cell growth and/or increased biomass (Chiboub et al, 2016). The Cd (II) bioaccumulation by strain FM-2 demonstrated in the present work is therefore consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(strain I10). Furthermore, intracellular Cd (II) bioaccumulation was found to be greater than that in the cell wall, demonstrating that Cd (II) bioaccumulation was related to cell growth and/or increased biomass (Chiboub et al, 2016). The Cd (II) bioaccumulation by strain FM-2 demonstrated in the present work is therefore consistent with previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…Cultures were incubated at 25°C with shaking at 200 rpm for 1, 3, 5, and 7 days. As described previously (Chiboub et al, 2016) with some modifications, cultures were centrifuged (8,000 rpm for 5 min at 4°C) and pellets were washed three times with sterile distilled water to remove free heavy metal ions. Pellets were then treated with 10 mM sterile EDTA at 25°C with agitation at 200 rpm for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The phytohormone production by PGPB is shown to play a key role in plant–bacterial interactions and plant growth in contaminated soils by heavy metals [53]. In fact, many heavy metals resistant bacteria were capable of producing phytohormones such as auxin IAA even under stress conditions [54], [55]. Thus, the observed plant growth promotion under Pb stress after inoculation of plant with P. fluorescens was attributed to bacterial IAA production and excretion [56].…”
Section: Resultsmentioning
confidence: 99%
“…The production of IAA by strain YH1 is higher (>100 μg ml −1 ) than most rhizobial stains previously reported and can be considered as an IAA-overproducer (Chiboub et al, 2016; Yu et al, 2017). It is observed that negative impact of metal accumulation inside plant tissues could be mitigated by the application of IAA (Nadeem et al, 2015).…”
Section: Discussionmentioning
confidence: 72%